Thresholds of handgrip strength for all-cause mortality in patients with chronic kidney disease: a secondary systematic review with dose-response meta-analysis - Hao Chen; Fan Zhang; Liuyan Huang; Yan Bai; Yifei Zhong; Yi Li (Renal Failure)
Background Although handgrip strength is associated with all-cause mortality in patients with chronic kidney disease (CKD), whether this relationship is dose-related is unknown. Therefore, we examined dose-response relationships between handgrip strength and all-cause mortality in CKD patients based on previous studies by meta-analysis.Methods Data sources included three electronic databases (PubMed, Web of Science, and Embase) from inception through October 2023. The included cohort was a CKD population not limited to disease stage, and their handgrip strength was objectively measured. Two researchers independently screened studies, extracted data, and assessed the risk of bias. We utilized estimates of handgrip strength categories using robust-error meta-regression (REMR), pooled study-specific estimates, and established dose-response relationships. Outcomes of interest included only all-cause mortality.Results A total of 18 studies with 4810 participants (aged 47–71 years) were included. REMR modeling showed a U-shaped trend of association between handgrip strength and all-cause mortality in patients with CKD. Higher handgrip strength values, from 10 kg to approximately 28 kg, were associated with lower mortality risk. After that, the risk of death increased slightly.Conclusion A U-shaped association exists between handgrip strength and all-cause mortality risk in CKD patients. Future studies with quantitative measurements for each CKD stage will help to determine precise relative risk estimates between handgrip strength and mortality risk in patients with different stages of CKD.